2014
DOI: 10.1097/sla.0b013e31829d3969
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Sacral Nerve Stimulation for Fecal Incontinence at 5 Years

Abstract: On an ITT analysis, 42.6% of patients reported favorable outcomes at 60 months. Patient's age, improvement of urge incontinence during PNE, and sustained efficacy during the first 6 months after implantation are some of the predictors identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
48
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 28 publications
(20 reference statements)
10
48
3
Order By: Relevance
“…Maeda et al found that increasing age decreases the odds of a successful outcome with SNS by 4.3 % a year [73]. George et al conducted a study examining the role of SNS in patients 65 years of age and older.…”
Section: Sacral Nerve Stimulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Maeda et al found that increasing age decreases the odds of a successful outcome with SNS by 4.3 % a year [73]. George et al conducted a study examining the role of SNS in patients 65 years of age and older.…”
Section: Sacral Nerve Stimulationmentioning
confidence: 97%
“…It is still unclear if SNS would be appropriate for patients with dementia, who are wheelchair bound, or in a nursing home. In addition, SNS is a high maintenance procedure and requires frequent office visits to properly manage issues of efficacy and adverse events [73]. Patients must be able to evaluate their improvement and vocalize their concerns regarding SNS implantation to maintain efficacy.…”
Section: Sacral Nerve Stimulationmentioning
confidence: 98%
“…the frequency of surgical complications (tables 3 and 4 and appendix table 5) ranged from 0% to 32% in radiofrequency anal sphincter remodeling, [48][49][50][51][52][53] 21% to 74% in aCe, 54-57 5% to 27% with sphincteroplasty, 13,37,42-45,58-66 2% to 93% with sns, 13,29,30,36,41,47,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] 8% to 64% with other surgeries, 33,38,39,86 and 22% to 100% with sphincter replacement. 13,32,46,[87][88][89][90][91][92][93][94][95][96][97][98]…”
Section: Other Surgeries and Mixed Treatment Comparisonsmentioning
confidence: 99%
“…table 4 and appendix table 5), and 3% to 24%41,47,[67][68][69]71,72,[74][75][76][77][78][79][80][81]85 of patients had the device explanted. aCe, sphincter repair, and sphincter replacement had more severe complications (wound infection, stenosis, bowel obstruction, sepsis, and fistula; appendix table 5).…”
mentioning
confidence: 99%
“…Multiple studies over the last year have reported long-term outcomes, demonstrating that the majority of patients treated with SNS experience lasting improvements in incontinence and QOL with minimal complications at mean follow ups ranging from 3-9 years [22][23][24]. Multiple studies over the last year have reported long-term outcomes, demonstrating that the majority of patients treated with SNS experience lasting improvements in incontinence and QOL with minimal complications at mean follow ups ranging from 3-9 years [22][23][24].…”
Section: Nerve Stimulation Techniquesmentioning
confidence: 99%